Literacy Problems of Reading, Writing and Numeracy through a Student Approach at SLB Negeri 2 Buleleng - Setiawati, Ni Kadek; Kadek Prima Dwijayanti AK; Pertiwi, Komang Diah Ari; Werang, Basilius Redan (LPPM Universitas Dhyana Pura, 2025)
This study aims to analyze the challenges of reading, writing, and numeracy literacy among students at Special Needs Schools (SLB) with mild intellectual disabilities (mental retardation) as an effort to improve life skills and educational inclusion. This research used qualitative methods with a descriptive approach, conducted at SLB Negeri 2 Buleleng. The focus of the research included students' reading, writing, numeracy, obstacles experienced by students with special needs, and teachers' approaches to learning. Data collection techniques included observation, interviews, and documentation, which were then analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results revealed two categories of significant barriers. First, intrinsic cognitive barriers include difficulty understanding abstract concepts such as ratios and number patterns, below-average IQ, and information processing limitations that impact learning speed and memory. Second, learning and environmental challenges include low practice, inappropriate teaching methods, limited infrastructure, a lack of trained teachers, low reading interest, and social inequality. This research identifies the benefits of literacy, writing, and numeracy in improving academic skills, communication, daily independence, self-confidence, social interaction, logical thinking, vocational skills, and motor and visual perception. Mastery of literacy, writing, and numeracy has proven crucial for students with intellectual disabilities to live more independently and less dependent on others for assistance. Recommended improvement strategies include the development of adaptive learning media, structured literacy programs, teacher and parent training, multi-stakeholder collaboration, and the use of varied learning methods. Recommendations include prioritizing the provision of qualified teachers, technology and internet access, collaboration between the government, tourism sector, and the community, and transparent oversight of educational programs. This holistic approach is expected to create a learning environment that supports the development of numeracy literacy for sustainable educational inclusion.